BIOPREPARATION AND PROCESSING TECHNOLOGY TO INCREASE THE STORAGE OF POTATO PRODUCTS - Tursunmurotov, Sherzod Shoniyozivich (Educational Research in Universal Sciences, 2023)
“Technology of prolonging the storage period of potatoes with the help of Zamin-M biopreparation” on the effect of processing with the biopreparation Zamin-M (based on Bacillus subtilis, Bacillus megaterium and Pseudomonas stutzeri strains) on the storage period and the technology of extending the storage period. information is provided. The dependence of the storage period of the potato tuber with biopreparation on the temperature regime is shown. Research on the preservation of potato tubers was conducted at Termiz State University.